Islamic financial markets and institutions: challenges, financial stability and inclusivity - Taghizadeh-Hesary, Farhad; Mohd Thas Thaker, Hassanudin; Bhatti, M Ishaq; Allah Pitchay, Anwar (Springer Nature Singapore, 2025)
In recent years, Islamic financial institutions have experienced substantial growth, particularly in Asia and the Middle East, with a focus on financial innovation and the advancement of asset securitisation. This growth, crucial for the future development of Islamic financial institutions (IFIs), necessitates a robust regulatory framework and effective monetary policies. The book examines IFIs’ complexities in maintaining compliance with Islamic law while ensuring financial stability and inclusivity. Islamic Financial Markets and Institutions: Challenges, Financial Stability, and Inclusivity examines the challenges of limited financial inclusion, poverty, non- Muslim ownership dominance, and the complexities of emerging Islamic financial products. Emphasis is placed on the need for a legal and regulatory structure that ensures transparency, uniformity, and predictability, advocating for the incorporation of standards into supervisory frameworks. The book addresses the challenges of strengthening domestic regulatory structures, ensuring the stability of Islamic finance, and integrating Islamic finance into the global financial system’s regulatory framework. Despite signi!cant expansion prospects, the book argues that Islamic finance necessitates a legal and regulatory framework to mitigate the unique risks associated with Islamic financing. The book consists of 15 chapters and is structured into three Parts: Navigating Challenges in Islamic Financial Markets and Institutions, Ensuring Financial Stability Within Islamic Finance Frameworks, and Promoting Inclusivity Through Islamic Financial Markets.